Dissecting the Subcellular Localization, Intracellular Trafficking, Interactions, Membrane Association, and Topology of Citrus Leprosis Virus C Proteins - Leastro, Mikhail Oliveira; Kitajima, Elliot Watanabe; Silva, Marilia Santos; Resende, Renato Oliveira; Freitas-Astúa, Juliana (Frontiers in Plant Science, 2018)
Citrus leprosis (CL) is a re-emergent viral disease affecting citrus crops in the Americas, and citrus leprosis virus C (CiLV-C), belonging to the genus Cilevirus, is the main pathogen responsible for the disease. Despite the economic importance of CL to the citrus industry, very little is known about the performance of viral proteins. Here, we present a robust in vivo study around functionality of p29, p15, p61, MP, and p24 CiLV-C proteins in the host cells. The intracellular sub-localization of all those viral proteins in plant cells are shown, and their co-localization with the endoplasmic reticulum (ER), Golgi complex (GC) (p15, MP, p61 and p24), actin filaments (p29, p15 and p24), nucleus (p15), and plasmodesmata (MP) are described. Several features are disclosed, including i) ER remodeling and redistribution of GC apparatus, ii) trafficking of the p29 and MP along the ER network system, iii) self-interaction of the p29, p15, and p24 and hetero-association between p29-p15, p29-MP, p29-p24, and p15-MP proteins in vivo. We also showed that all proteins are associated with biological membranes; whilst p15 is peripherally associated, p29, p24, and MP are integrally bound to cell membranes. Furthermore, while p24 exposes an N-cytoplasm-C-lumen topology, p29 and p15 are oriented towards the cytoplasmic face of the biological membrane. Based on our findings, we discuss the possible performance of each protein in the context of infection and a hypothetical model encompassing the virus spread and sites for replication and particle assembly is suggested.